Corporate Social Responsibility by Mineral Foundation of Goa - A Study - Pednekar, Achut P. (Prabandhan: Indian Journal of Management, 2011)
Corporate social responsibility has since long been a hot topic globally. CSR award winners have typically engaged in green activism and philanthropy. Environmental concern has earned many a company's ISO 14001 certification. Most of the educational institutes, research centres and medical facilities have been set up under the patronage of the industry. But these efforts, though genuine, were individual and sporadic. Hence, the industry set together to conceptualize the Mineral Foundation of Goa, a society set up as a collective approach to address the social and environmental issues concerning the community living in the mining belts of Goa. Understanding of the fact that intervention in areas where one's core business has an influence is the bottom-line of CSR, and this has led the industry to come together and give birth to a body that would work exclusively in the mining areas of Goa. In this paper, a study has been undertaken to analyze the various programmes contributing towards economic growth, employment generation, social upliftment of communities and environment conservations in the mining belt. This study is an effort to find out in what way, and to what extent, the mining companies contribute to the society through Mineral Foundation of Goa. The study is based on the theoretical and analytical aspects of health, which is one of the activities of the social responsibility of MFG towards general public in the mining areas of Goa.